2022
DOI: 10.1177/02601060221082368
|View full text |Cite
|
Sign up to set email alerts
|

The nutritional status of community-dwelling elderly in Lesotho and factors associated with malnutrition

Abstract: Objective: The elderly living in Africa are prone to malnutrition which is complicated by the high prevalence of poverty. This study assessed the nutritional status of the elderly and factors associated with malnutrition. Method: In a cross-sectional survey, the nutritional status of 300 participants aged 65 years and older was determined using the Mini Nutritional Assessment (MNA) questionnaire consisting of 18 questions. Socio-demographic data was obtained using a questionnaire. Results: Sixty-six percent we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Self-reported health status is a predictor of morbidity and mortality in older adults [50]. The association between poorer self-perceived health status and higher risk of malnutrition has been reported [51]. In the present investigation, a better self-perceived state of health decreased nutritional risk and malnutrition.…”
Section: Discussionsupporting
confidence: 51%
“…Self-reported health status is a predictor of morbidity and mortality in older adults [50]. The association between poorer self-perceived health status and higher risk of malnutrition has been reported [51]. In the present investigation, a better self-perceived state of health decreased nutritional risk and malnutrition.…”
Section: Discussionsupporting
confidence: 51%
“…Thus, CVD may cause a lower subjective health status and psychological stress or depression [ 41 ]. A study with Portuguese older adults attending senior centers showed reports that both CVD and lower self-reported health status were associated with higher nutritional risk [ 18 ], and the association between poorer perceived health status and higher risk of malnutrition has also been reported elsewhere [ 42 ]. In addition, for individuals with CVD, the MNA score may be affected due to the recommendation to reduce the consumption of red meat [ 43 ] if not replaced by other protein sources.…”
Section: Discussionmentioning
confidence: 92%
“…Living in poverty negatively impacts cognitive and socioemotional processes commonly associated with healthy aging and it is considered a determining factor for social exclusion (Niedzwiedz et al, 2016) as it leads to inequalities and barriers to accessing public services (Price et al, 2018). Living in poverty has been associated with malnutrition (Dufe Turkson et al, 2022), greater functional limitation (Boggatz et al, 2010), higher mortality rates and an increased number and duration of hospital readmissions (Landon et al, 2023; Minhas et al, 2023). Living in poverty can also increase the prevalence of multiple chronic conditions (Choi et al, 2020; Minhas et al, 2023; Mira et al, 2023) and antibiotic prescribing rates (Tarkhashvili, 2023).…”
Section: Introductionmentioning
confidence: 99%